Estudio de factibilidad para la creación de una empresa productora y comercializadora de maletines elaborados en cuero (2018)
The feasibility study for the creation of a production and marketing company of briefcases made of leather in the city of Bogotá D.C., analyzing and identifying the most relevant factors of the fashion industry, which includes the Moroccan subsector. Based on the above, a market study is carried out, where the needs of potential consumers and the target market are identified, together with a marketing plan; in the technical-operative study, the process to comply with the production of briefcases was standardized; in the administrative study, an organizational analysis was carried out from which the respective strategic planning arose and responsibilities were assigned in the different positions of the company; In the legal study, the procedures for the constitution and operation of the company were investigated. A Colombian technical guide is prepared to identify hazards and assess risks, an evaluation plan and management of environmental impacts. Finally, in the financial study, the initial investment and project financing are calculated, evaluating indicators such as the net present value (NPV), which yields $ 1,745,515 as the result, the internal rate of return (IRR) that has a value of 22.05%, a profitability margin of 2.05% and a cost benefit ratio greater than 1.